The interprofessional organizations: From the need of establishment to the need of development and affirmation - Ioan-Niculae Alecu; Ana-Maria Georgiana Stroe (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
Through the present study it aims to represent the actual image of the interprofessional organizations on product chain in Romania, reflecting briefly the establishment and development issues. In the context of the reorganization of entire agrifood production system, in dealing with future crises, whatever is their nature, it's needed to seriously manage the organizational issues and to present them as a useful tool for increasing the access to new markets for producers and to offer local products quality to consumers in Romania both. Using the documentation method it was obtained an overview of the relationship between the need of affirmation and the real need to convert the interprofessional organizations in Romania in functional structures. The Ministry of Agriculture and Rural Development recognized till now only five IPO but the analysis and the directly involved interprofessional organizations opinions exchanges, it was emerged some primordial issues in order to improve the legislation of interprofessional organizations on product chain. The interprofessional organizations on product chain are meant, almost in ingrate way, to be interposed between the pressing help need in the development of intra-community trade relationships and the stiffness required by the legislation.
Keywords: 330; interprofessional organisations; agrifood sector; legislation; need; development